1990
DOI: 10.1093/ije/19.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Personal Cost of Illness due to Some Major Water-Related Diseases in an Indian Rural Population

Abstract: Afield study, aimed at measuring the personal cost of illness from five major water-related diseases was undertaken in a rural area of Uttar Pradesh (India) in 1981-82. The diseases included in the study were-entericfever, acute diarrhoeal diseases, infective hepatitis, conjunctivitis and scabies. The measurement of \he cost of illness included information on losses in productivity and treatment costs. The annual costs of illnesses per 100 people in 1981 were Rs 7353

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Families in endemic areas spend a substantial portion of income on treatments, restricting available funds for food and essential commodities [15], [16]. Direct costs relate to treatments, missed employment, frequent healthcare consultations, and management of hospitalised cases including institutional outbreaks.…”
Section: Why Is Scabies Important?mentioning
confidence: 99%
“…Families in endemic areas spend a substantial portion of income on treatments, restricting available funds for food and essential commodities [15], [16]. Direct costs relate to treatments, missed employment, frequent healthcare consultations, and management of hospitalised cases including institutional outbreaks.…”
Section: Why Is Scabies Important?mentioning
confidence: 99%
“…This applies especially to peri-urban areas, which surround the larger metropolitan towns. People living in these areas often utilize contaminated surface water for drinking, recreation and irrigation (Verma and Srivastava 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A study in rural Mexico in 1994 suggested that ineffective treatment of scabies occurred in over half of cases, and that when travel, medical bills, and drugs were taken into account, this totaled a mean cost of 66 new pesos (US$24) for the patient over six months. 31 The cost was US$5.29 per capita per year, almost 4% of the average annual income of $113. The burden was great for pyoderma, where an average of 136 new pesos (US$52) was spent on ineffective treatment over a 6-month period.…”
Section: Economymentioning
confidence: 99%
“…74 An equivalent commitment by the Mectizan donation program to a scabies elimination plan would be crucial to keeping costs comparably low. In addition, with a couple of notable exceptions, 30,31 we know very little about the economic burden that scabies places on communities. For example, the schistosomiasis control initiative estimates its delivery costs to be as low as 25 pence per person per year.…”
Section: Using Traditional Health Systemsmentioning
confidence: 99%